2021
DOI: 10.1152/ajprenal.00625.2020
|View full text |Cite
|
Sign up to set email alerts
|

Metformin ameliorates bladder dysfunction in a rat model of partial bladder outlet obstruction

Abstract: Alteration of bladder morphology and function was the most important consequence of bladder outlet obstruction (BOO). Using a rat model of partial bladder outlet obstruction (pBOO), we found that rats treated with metformin showed lower baseline pressures with reduced inflammatory reaction in early phase (2 weeks) after pBOO. NLRP3 inflammasome pathway was inhibited in pBOO rat bladders with the treatment of metformin in early phase. Metformin reduced the activity of NLRP3 in primary urothelial cells. In chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…This is one of limitations of the present study. In another aspect, BOO surgery used in this study caused bladder wall remodeling in rats, including hypertrophy and fibrosis, which is also the major characters of human BOO [ 50 ], meanwhile, this model has been applied in many similar reports [ 51 , 52 ]. We have demonstrated a role of circPVT1 on BOO development in animal model and cell-based model, but its application to human BOO were still obscure.…”
Section: Discussionmentioning
confidence: 99%
“…This is one of limitations of the present study. In another aspect, BOO surgery used in this study caused bladder wall remodeling in rats, including hypertrophy and fibrosis, which is also the major characters of human BOO [ 50 ], meanwhile, this model has been applied in many similar reports [ 51 , 52 ]. We have demonstrated a role of circPVT1 on BOO development in animal model and cell-based model, but its application to human BOO were still obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a highly regulated catabolic process that maintains cellular homeostasis in response to various damaged, defective, or unwanted stimuli ( Geir et al, 2005 ; Li et al, 2016 ; Daniel et al, 2018 ; Nam et al, 2019 ). Increasing evidence suggests that autophagy is closely related the bladder remodeling secondary to BOO due to its double-edged sword role in pro-cell survival and the pro-cell death properties ( Chen et al, 2021 ). Our previous study has demonstrated that autophagy regulated the biological function of BSMCs under HP ( Chen et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…With regard 907 to metformin effect on the bladder contractility, there were only few meeting reports and there was insufficient studies on the mechanism of action of metformin on the urinary bladder of rats. [9,10,11]. Studied that differential effects of metformin in rats' urinary bladder and other different tissues.…”
Section: Discussionmentioning
confidence: 99%